Ergonomski vidiki razvoja izdelkov: 2. posodobljena in razširjena izdaja - Dolšak, Bojan; Kaljun, Jasmin Kaljun (2021)
Ergonomic Aspects of Product Design: 2nd Updated and Expanded Edition. The textbook is dealing with product ergonomics both from the point of view of the development engineer, who of course has to ensure the functionality of the product, and from the point of view of the designer, who should ensure that the product is also aesthetically perfect. The purpose of the textbook is not to provide empirical data, but to introduce basic concepts and present mutual relationships and recommendations that can help engineers and designers to develop products with a focus on ergonomic and aesthetic value. In the second edition, a completely new chapter is added, which deals with inclusive design and its most important aspects. In most cases, these are in line with the ergonomic aspects of product development, with one important difference. Instead of adapting the product to limited target population of users, the goal of inclusive design are products suitable for the widest possible population.
Keywords: product development; ergonomics; anthropometry; aesthetics; recommendations; inclusive design